الدراسة النحوية عن الاشتغال وأساليبه فى القرآن جزء عمّ - Muh. Abrar; Asriani Asriani; Abdul Hamid (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This research shows the definition of the worker's work from the work and its provisions, and it shows the surahs that contain the worker's work from the work in the thirtieth part of the Qur'an. As for the research methods that the researcher uses to study this writing, it is the qualitative research approach, in terms of its type. From this research, the researcher knew that the worker's occupation of the work is a preceding object, even if two sentences are nominative and accusative. The nominative is like the subject and the accusative is like the object. Also, the researcher knew that six surahs that contain the preoccupation of a worker from the work in the thirtieth part of the Qur’an, namely, Surat Al-Duha, Surat Al-Shams, Surat Al-Fajr, Surat Al-Naza’at, Surat ‘Abs, and Surat Al-Naba’. The researcher found that the worker is busy with what is done in the thirtieth part of the Qur’an. There are ten verses that contain work, which are two verses in Surat Al-Duha, verse: 9 and 10, three verses in Surat Al-Shams, verses: 5,6, and 7, one verse in Surat Al-Fajr, verse: 15, one of the verses in Surat Abas, verse: 20, two verses in Surat Al-Naza'at, verses: 30 and 32, and the other from the verse of Surat Al-Naba, verse: 29.